Anxiety and depression among out-of-hospital cardiac arrest survivors. (December 2015) - Lilja, G.; Nilsson, G.; Nielsen, N.; Friberg, H.; Hassager, C.; Koopmans, M.; Kuiper, M.; Martini, A.; Mellinghoff, J.; Pelosi, P.; Wanscher, M.; Wise, M.P.; et al.
Abstract: Aim: Survivors of out-of-hospital cardiac arrest (OHCA) may experience psychological distress but the actual prevalence is unknown. The aim of this study was to investigate anxiety and depression within a large cohort of OHCA-survivors. Methods: OHCA-survivors randomized to targeted temperature of 33 °C or 36 °C within the Target Temperature Management trial (TTM-trial) attended a follow-up after 6 months that included the questionnaire Hospital Anxiety and Depression Scale (HADS). A control group with ST-elevation myocardial infarction (STEMI) completed the same follow-up. Correlations to variables assumed to be associated with anxiety and depression in OHCA-survivors were tested. Results: At follow-up 278 OHCA-survivors and 119 STEMI-controls completed the HADS where 24% of OHCA-survivors (28% in 33 °C group/22% in 36 °C group, p  = 0.83) and 19% of the STEMI-controls reported symptoms of anxiety (OR 1.32; 95% CI (0.78–2.25), p  = 0.30). Depressive symptoms were reported by 13% of OHCA-survivors (equal in both intervention groups, p  = 0.96) and 8% of STEMI-controls (OR 1.76; 95% CI (0.82–3.79), p  = 0.15). Anxiety and depression among OHCA-survivors correlated to Health-Related Quality-of-Life, and subjectively reported cognitive deterioration by patient or observer. In addition, depression was associated with a poor neurological outcome. Conclusion: One fourth of OHCA-survivors reported symptoms of anxiety and/or depression at 6 months which was similar to STEMI-controls and previous normative data. Subjective cognitive problems were associated with an increased risk for psychological distress. Since psychological distress affects long-term prognosis of cardiac patients in general it should be addressed during follow-up of survivors with OHCA due to a cardiac cause. ClinicalTrials.govNCT01020916 /NCT01946932 .